1982
DOI: 10.1073/pnas.79.23.7460
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a major cluster of lymphocyte differentiation antigens on murine chromosome 2.

Abstract: The region of chromosome 2 between H-13 and H-3 has been shown to contain loci coding for a variety of other alloantigens, including Ly-4 and the locus coding for (82-microglobulin. Herein we show that and Ly-il are coded for by genes in a segment of chromosome 2 adjacent to the H-3-H-13 region and that this segment of chromosome also contains the tightly linked loci coding for antigens Ala-i, DAG, H9/25, H-30, Ly-8, and ThB. In addition, at least one locus (and probably more) affecting susceptibility to leuk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
13
1

Year Published

1983
1983
1987
1987

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 22 publications
0
13
1
Order By: Relevance
“…Other studies from our laboratory, primarily designed to map lymphocyte antigen-encoding loci, indicated that viral sequences are often found adjacent to histocompatibility loci and genes encoding several Ly (H/Ly) antigens (1,7,8), but these studies did not address the issue directly because serological reagents were used. The current report directly demonstrates that endogenous viral sequences are often found tightly linked to H/Ly loci and viral inducibility or susceptibility loci.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies from our laboratory, primarily designed to map lymphocyte antigen-encoding loci, indicated that viral sequences are often found adjacent to histocompatibility loci and genes encoding several Ly (H/Ly) antigens (1,7,8), but these studies did not address the issue directly because serological reagents were used. The current report directly demonstrates that endogenous viral sequences are often found tightly linked to H/Ly loci and viral inducibility or susceptibility loci.…”
mentioning
confidence: 99%
“…These latter associations between viral sequences, susceptibility loci, .and H/Ly loci also occur for at least some of the viral sequences mapped in the previous section to chromosome 2. A locus conferring susceptibility to RadLV-induced leukemia, RLVil-1, is adjacent to H-3 (8), and the major locus involved in susceptibility to leukemia induction by split doses of irradiation, Riil-, is next to H-30 (8).…”
mentioning
confidence: 99%
“…The Ly-6 gene complex was initially mapped by genetic techniques to chromosome 9 (15) and was later reassigned to chromosome 2 (16). This paper reports the use of the Ly6E.…”
mentioning
confidence: 99%
“…A growing body of evidence also suggests that a series of cell surface antigens are encoded by genes on the second chromosome (11)(12)(13)(14)(15). At least one of these antigens is a manifestation of j32-microglobulin (32m), and it is possible that and H-3 antigens are also closely related to (32m (16)(17)(18).…”
mentioning
confidence: 99%